Potencial prognóstico da expressão das proteínas imunomoduladoras IDO, CD39 e CD73 na progressão do câncer de bexiga - Ferreira, Janaina Mendes (2021)
Introduction: Bladder cancer (BC) is the second most common tumor of the urinary system. Although 75% of cases have an initial non-muscle-invasive presentation (NMIBC) and can be treated curatively with organ preservation through endoscopic resection, about 75% present with recurrence and 20% progress to the muscle-invasive form (MIBC). Immunotherapy with intravesical BCG is used as an adjuvant therapy and reduces tumor recurrence and progression by 50%, but the other half of the cases will still have a recurrence of the neoplasm. MIBC, on the other hand, is treated by radical cystectomy and neoadjuvant chemotherapy, but at this stage the treatment has high perioperative morbidity and the 5-year survival is only 50%. The promising results of immunotherapies have encouraged new targets. Indoleamine 2,3-dioxygenase (IDO) is an enzyme that has immunomodulatory action in important physiological mechanisms, preventing an exacerbated response of the immune system. IDO is also expressed in tumors where it acts by inhibiting lymphocytic activity and thus promoting immune escape. CD39 and CD73 proteins also have immunosuppressive action and, like IDO, they have oncogenic action, as they favor the immune escape of the neoplastic cell. Although the role of IDO, CD39 and CD73 is not yet fully established, the expression of these molecules may have prognostic potential in BC. Objectives: To evaluate the protein expression of IDO, CD73 and CD39 in surgical specimens of CBNMI and CBMI and to correlate with clinicopathological parameters. Material and methods: We retrospectively selected 88 patients with NIMBC treated by endoscopic resection and adjuvant BCG who had or did not have disease recurrence during the postoperative follow-up at Hospital Brigadeiro between 2012 and 2017. We also evaluated the expression of these markers in a series of 77 patients with CBMI treated by radical cystectomy at the same time and location. Protein expression was evaluated semiquantitatively by immunohistochemistry in Tissue Micro Array containing three samples per case. We correlated the expression of these proteins with tumor grade, pathological stage, recurrence, smoking, treatment and disease progression. Results: Of the 162 patients who offered viable samples, 129 were men (79.6%) and 33 were women (20.4%). Most were elderly (70.4%>65 years old) and smokers (79.5%). As for the histological grade, 74% of the patients were of high grade and 26% of low grade. The high expression of IDO1 correlated with an early stage (NMIBC x MIBC) and with patients undergoing TUR (RTU x CR) (p<0.001). The high expression of CD39 was associated with NMIBC (p<0.001), the lower grade stage (Ta, T1 x T2, T3 and T4) and the RTU treatment (RTU x CR) (p<0.001). Regarding CD73, no clinical-pathological characteristics were associated. However, when combined with CD39 expression, low expression of CD39 and CD73 was associated with advanced BC. Regarding the treatment, the high expression of both was present in patients submitted to TUR in contrast to the low expression of both in the CR (p<0.001). Finally, the analysis of the correlation between the association of IDO, CD39 and CD73 expression proved to be significant (p<0.002). Conclusion: We propose that the analysis of IDO, CD39 and CD73 enzymes may be complementary biomarkers in the prognosis of BC.